Abstracts (Edited By Dr. Qasim Lateef Chaudhry) - Chaudhry, Qasim Lateef (Pakistan Journal of Ophthalmology, 2018)
Efficacy and Safety of Long-term Corticosteroid Eye Drops after Penetrating Keratoplasty: A Prospective, Randomized, Clinical Trial Shimazaki J, Iseda A, Satake Y, Shimazaki-Den S Ophthalmology 2012; 119: 668-73. Correlation between Clinical Features, Magnetic Resonance Imaging, and Histopathologic Findings in Retinoblastoma: A Prospective Study Chawla B, Sharma S, Sen S, Azad R, Bajaj MS, Kashyap S, Pushker N, Ghose S Ophthalmology 2012; 119: 850-6. Outcomes of sulfur hexafluoride (SF6) versus perfluoroethane (C2F6) gas tamponade for nonposturing macular – hole surgery Rahman R, Madgula I, Khan K Br J Ophthalmol 2012; 96: 185-8.